Library of Congress Classification training - Suja', Balqis (2010)
This is a one day lecture of a four-day programme, focussing on LCC. The contents are divided into: Overview of LCC; LCC schedules and tables; LCC finding numbers; LCC number building and classification practice; shelflisting, and ended by hands on exercise.